2018
DOI: 10.1037/neu0000443
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting hemispheric asymmetries for emotional processing from event-related potentials and behavioral responses.

Abstract: We conclude that there is no correspondence between behavioral and electrophysiological results concerning asymmetries for emotion processing, and that the VH and the RHH are not mutually exclusive. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 39 publications
(60 reference statements)
4
34
1
Order By: Relevance
“…Thus, three distinct components were found: P1 (∼110 ms), N1 (∼170 ms) and P2 (∼270 ms), with corresponding group average time windows of 90-120, 140-190 and 200-300 ms. These components were also reported in previous literature to be early (P1) and later subsequent emotion processing correlates (Prete et al, 2018). A late P300 was identified in some individuals, however it was not present in all participants and, therefore, was excluded from further analysis.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Thus, three distinct components were found: P1 (∼110 ms), N1 (∼170 ms) and P2 (∼270 ms), with corresponding group average time windows of 90-120, 140-190 and 200-300 ms. These components were also reported in previous literature to be early (P1) and later subsequent emotion processing correlates (Prete et al, 2018). A late P300 was identified in some individuals, however it was not present in all participants and, therefore, was excluded from further analysis.…”
Section: Discussionsupporting
confidence: 68%
“…However, these findings may be contradictory to the valence hypothesis (VH) that suggests LH dominance for positive information processing and right hemisphere (RH) dominance for negative emotion processing (Baijal and Srinivasan, 2010). However, Prete et al (2018) argued that these two hypotheses are not mutually exclusive and while their combined behavioral and ERP data showed RH dominance for negative emotions processing, LH dominance in behavioral data and RH superiority in ERP findings were found for positive emotions. According to our ERP results, emotion word processing is greater in the RH, as indicated by our later, P2 component amplitude.…”
Section: Discussionmentioning
confidence: 91%
“…Other findings suggest a dominance of right hemisphere for the processing of all kinds of emotions (Gainotti, 2018), although other studies found an advantage of right hemisphere only for conscious, but not unconscious, perception of negative emotion, but not for positive ones (Smith & Bulman-Fleming, 2005). Nevertheless, these theories are not mutually exclusive in the processing of facial emotional expression (Prete, Capotosto, Zappasodi, & Tommasi, 2018) and the role played by the temporal lobe would be dependent on both hemispheres (Killgore & Yurgelun-Todd, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…is not a strict correspondence between behavioral evidence and ERP components regarding hemispheric asymmetries for emotions (Prete, Capotosto, Zappasodi, & Tommasi, 2018). However, a recent study has reported hemispheric asymmetries in emotion processing (Wyczesany, Capotosto, Zappasodi, & Prete, 2018), and subliminal emotional LSF information affects early visual processing (Prete, Capotosto, Zappasodi, Laeng, & Tommasi, 2015).…”
Section: M Itati O N Smentioning
confidence: 94%
“…Furthermore, in a proposed face‐processing model, both facial identity and expression are first encoded by a mechanism that is not completely separated within a single visual perceptual representation (Calder & Young, 2005). It was reported that there is not a strict correspondence between behavioral evidence and ERP components regarding hemispheric asymmetries for emotions (Prete, Capotosto, Zappasodi, & Tommasi, 2018). However, a recent study has reported hemispheric asymmetries in emotion processing (Wyczesany, Capotosto, Zappasodi, & Prete, 2018), and subliminal emotional LSF information affects early visual processing (Prete, Capotosto, Zappasodi, Laeng, & Tommasi, 2015).…”
Section: Limitationsmentioning
confidence: 99%